Dual pore‐size sieving in a novel oxygenate‐pillared microporous adsorbent for C6 alkane isomers separation. Issue 3 (29th October 2022) - Su, Yun; Chen, Rundao; Zhang, Peixin; He, Xiao; Liu, Xing; Liu, Yuan; Xiong, Hanting; Zhao, Zhiwei; Luo, Junhui; Chen, Jingwen; Chen, Shixia; Zeng, Zeling; et al.
Abstract: Adsorbents executing molecular sieving mechanisms for the efficient separation of n ‐hexane (C6) alkane isomers require delicate pore size control, but afford unsatisfactory single‐component separations according to their branch degrees. Herein, we report a novel oxygenate‐pillared microporous adsorbent, MoOFOUR‐Co‐tpb, ([Co(tpb)2 MoO4 ], tpb = 1, 2, 4, 5‐tetra(pyridin‐4‐yl) benzene), with three gourd‐shaped channels for dual pore‐size sieving of C6 isomers. In particular, MoOFOUR‐Co‐tpb excludes 2, 2‐dimethylbutane, while 3‐methylpentane (3MP) can enter one channel showing a high uptake of 82.6 mg g −1, contrasting to the n ‐hexane ( n HEX) adsorption by two channels (136 mg g −1 ). This dual pore‐size control strategy renders a record high equilibrium–kinetic combined selectivity for n HEX/3MP (30.2). Moreover, three‐ and five‐component breakthrough experiments confirm the practical separation performances and cycling stability. Multiple theoretical simulations reveal the separation mechanism and adsorption sites.